EFFECTIVENESS OF METABOLIC AND NEUROPROTECTIVE FOR NEWBORNS WITH BIRTH ASPHYXIA DETERMINED BY ANALYZING FINDINGS OF CHILDREN EXAMINATION ACCORDING TO NEUROBEHAVIORAL MONITORING SCALE - Похилько, В.І. (World of Medicine and Biology, 2010)
This paper presents the results of randomized study of clinical effectiveness of a therapy approach including the administration of both Lipin and Cerebrocurin® as compared to standard therapy for newborns with birth asphyxia. It has been established the introduction of both Lipin and Cerebrocurin® in standard therapy for newborns with hypoxic-ischemic CNS disturbances caused by perinatal asphyxia promotes adaptive and compensatory responses in children under the influence of stress factors and facilitates more rapid recovery of their active and passive tonus.